Dynamic changes of endogenous phytohormones and carbohydrates during spontaneous morphogenesis of Centaurium erythraea Rafn - Trifunović-Momčilov, Milana; Motyka, Václav; Marković, Marija; Milovančević, Marija; Filipović, Biljana; Dobrev, Petre I.; Subotić, Angelina (Frontiers in Plant Science, 2024)
Common centaury (Centaurium eryhtraea Rafn) is a medicinal plant species with vigorous morphogenic potential in vitro. The process of spontaneous shoot regeneration in a solid root culture is characteristic for this plant species. In this context, the aim of this work was to investigate the dynamic changes of endogenous phytohormones and carbohydrates content in root explants at different time points (0, 2, 4, 7, 14, 21, 28, and 60 days) during spontaneous centaury morphogenesis in vitro. Detailed analysis of cytokinins (CKs) showed that trans-zeatin (tZ) was the major bioactive CK at all time points. The corresponding riboside, tZ9R, was also determined in the majority of the identified transport forms, at all time-points. Further analysis of endogenous auxin revealed a significant increase in endogenous indole-3-acetic acid (IAA) after 21 days, when a huge jump in the ratio of IAA/bioactive CKs was also observed. The maximum total soluble sugar content was measured after 14 days, while a significant decrease was determined after 21 days, when the first regenerated adventitious shoots appeared. This undoubtedly indicates an increased energy requirement prior to the actual regeneration of the shoots. The obtained results indicate that the period from day 14 to day 21 involves the most dramatic disturbances in endogenous bioactive CKs, IAA and carbohydrate balance, which are very important and valuable factors for the onset of shoot regeneration.